ECONOMIC SECURITY OF SOCIAL CAPITAL OF THE COUNTRY - HUROCHKINA, Viktoriia; KALACH, Hanna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The economic security of the country’s social capital acts as the basis of society’s stability and affects various aspects of the country’s life and development. Social capital is formed on the basis of common networks of social interaction, trust, cooperation, partnership and stable relations between citizens, public organizations and the government. The authors of the article present the essence of economic security of social capital and its distinctive features from social security in the system of socio-economic development of the country. The interpretation of the concept of "infinition of social capital" as an endless innovative flow of development and expansion of social capital in society is presented. It is characterized that the definition of social capital is based on the growth of social capital and is maintained and developed through social interactions, cooperation and trust between citizens and groups. The article discloses the conditions for the formation of the system of economic security of social capital, which is the basis of the state economic strategy aimed at the effectiveness and expansion of social relations and networks in the formation of economic stability and development, to achieve stability and welfare of society. The principles of the scientific and methodical approach to measuring the economic security of the country’s social capital are determined and a set of indicators characterizing the economic stability of society is outlined. It was determined that a distinctive feature of the economic security of social capital from social security in the system of socio-economic development of the country is the focus on the use of social relations and networks to support economic stability and development, while social security is aimed at ensuring minimum social standards and protecting citizens from risks, related to loss of income and social needs. Both concepts are important for the functioning of society, and they can interact with each other, affecting the well-being and sustainability of society.